Three-dimensional propulsion characteristics of counter-phase oscillating dual-foil propulsor. (15th October 2021) - Wang, Jiadong; Liu, Pengfei; Chin, Christopher; He, Guanghua; Mo, Weijie
Abstract: A three-dimensional computational study was conducted on the propulsive performance of auto-pitch wing-in-ground effect oscillating foil propulsors (APWIGs) using an unsteady Reynolds Averaged Navier-Stokes solver. This novel propulsor is characterized as the combination of dual-foil configuration and spring-based pitching motion. Both the counter-phase oscillating dual-foil arrangement with produced wing-in-ground (WIG) effect and the auto-pitch mechanism based on attached torsional springs are expected to be favorable for performance improvement. To clearly identify the role of two concerned parameters for APWIGs, the study was divided into two parts of simulations to examine aspect ratio and torsional spring stiffness separately. Firstly, the effect of aspect ratio on the hydrodynamic characteristics was investigated by a fully prescribed oscillating dual-foil configuration. The current computations covering a wide range of aspect ratio from 1 to 10 indicated that the three-dimensional effect tends to dominate the propulsion hydrodynamics with a value of lower than 2. The maximum drop of 14.85% in propulsive efficiency due to the finite-span effect was found at the aspect ratio of 1, while a moderate aspect ratio of 4 leads to an acceptable efficiency loss of 3.22%. Secondly, the three-dimensional hydro-elasticity characteristics of APWIGs as a function of spring stiffness were studied by employing a fixed aspect ratio. A relatively low aspect ratio in which the finite-span effect is still dominant was selected to compare the three-dimensional simulations with two-dimensional predictions. It was observed that the torsional spring stiffness has a significant influence on both hydrodynamic performance and vortex structures of finite-span APWIGs. There exists an optimum spring stiffness for finite-span APWIGs corresponding to the highest efficiency, which resembles the hydro-elasticity characteristics of two-dimensional cases. An averaged efficiency loss of around 10% was reported owing to the low-aspect-ratio effect for three-dimensional APWIGs. Highlights: Finite-span effect dominates flow hydrodynamics with aspect ratio below 4. Maximum efficiency drop of 14.85% was reported due to low-aspect-ratio effect. Spring stiffness has a significant effect on performance of finite-span APWIGs. Efficiency loss of around 10% was observed for low-aspect-ratio APWIGs. Wake topology of 3D oscillating foil is characterized as two sets of vortex rings.